Answers ( )

  1. Ответ:

    \frac{\sin{(60^o+\alpha)}-\frac{1}{2}\sin{\alpha}}{\cos{(60^o-\alpha)}-\frac{1}{2}\cos{\alpha}} = \frac{\sin{60^o}\cdot\cos{\alpha}+\cos{60^o}\cdot\sin{\alpha}-\frac{1}{2}\sin{\alpha}}{\cos{60^o}\cdot\cos{\alpha}+\sin{60^o}\cdot\sin{\alpha}-\frac{1}{2}\cos{\alpha}}=\frac{\frac{\sqrt{3}}{2}\cdot\cos{\alpha}+\frac{1}{2}\cdot\sin{\alpha}-\frac{1}{2}\sin{\alpha}}{\frac{1}{2}\cdot\cos{\alpha}+\frac{\sqrt{3}}{2}\cdot\sin{\alpha}-\frac{1}{2}\cos{\alpha}}=

    =\frac{\frac{\sqrt{3}}{2}\cdot \cos{\alpha}}{\frac{\sqrt{3}}{2}\cdot\sin{\alpha}}=ctg\alpha

Leave an answer

Browse

14:4+8*3-6:2*2+4:1 = ? ( )